Pengaruh Hubungan Kinerja, Likuiditas dan Return Saham Terhadap Deviasi Actual Growth Rate Dari Sustainable Growth Rate Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Adimas Wahyu Saputro; Agus Purwanto (Diponegoro Journal of Accounting, 2013)
Every company wants a high profit. This will increase sales growth. However, growth is not always profitable. If too fast the growth can put enormous pressure on the resources of the company. Whereas if the growth is too slow, the company considered less take the financial potential of existing firms. Therefore, the concept of sustainable growth rate can be sized for a maximum level of sales could rise without the company running out of financial resources. This study aims to empirically examine the effect of performance (ROA and price-to-book ratio), liquidity (current ratio and acid ratio) and stock returns to the deviation of actual growth rate of sustainable growth rate. This study uses multiple regression analysis with a sample of 49 companies listed on the Indonesia Stock Exchange (IDX) of the years 2009-2011. The results indicate that some determinants such as ROA, current ratio and acid ratio affect of the deviation of actual growth rate of sustainable growth rate. However, other factors, such as price to book ratio and stock return do not explain market value influence to the deviation of actual growth rate of sustainable growth rate because it represents fluctuations in the demand-supply company's stock price rather than the performance.